Dielectric function and degradation process of poly(triarylamine) (PTAA) - Sendner, Michael; Trollmann, Jens; Pucci, Annemarie (Organic electronics, 2014)
We investigated the optical properties and the degradation process of the organic p-type semiconductor poly(triarylamine) (PTAA) in the mid infrared region. The dielectric function of PTAA was determined in the spectral region of 700 up to 6000cm−1 by modeling ellipsometric measurements. Due to degradation at 65°C, PTAA thin films developed carbonyl and hydroxyl features in the infrared spectra. Degradation under 85%RH additionally led to absorption signals of water. A degradation of the bare gold substrates was also observed. For bare gold films, morphology changed upon degradation and adsorption of hydrocarbons from the ambience took place.